Biological Rhythms and Preeclampsia - Ditisheim, Agnès; Dibner, Charna; Philippe, Jacques; Pechère-Bertschi, Antoinette (Frontiers in Endocrinology, 2013)
The impact of impaired circadian rhythm on health has been widely studied in shift workers and trans-meridian travelers. A part from its correlation with sleep and mood disorders, biological rhythm impairment is a recognized risk factor for cardiovascular diseases and breast cancer. Preeclampsia is a major public health issue, associated with a significant maternal and fetal morbidity and mortality worldwide. While the risks factors for this condition such as obesity, diabetes, pre-existing hypertension have been identified, the underlying mechanism of this multi-factorial disease is yet not fully understood. The disruption of the light/dark cycle in pregnancy has been associated with adverse outcomes. Slightly increased risk for “small for gestational age” babies, “low birth weight” babies and preterm deliveries has been reported in shift working women. Whether altered circadian cycle represents a risk factor for preeclampsia or preeclampsia is itself linked with an abnormal circadian cycle is less clear. There are only few reports available, showing conflicting results. In this review, we will discuss recent observations concerning circadian pattern of blood pressure in normotensive and hypertensive pregnancies. We explore the hypothesis that circadian misalignments may represent a risk factor for preeclampsia. Unraveling potential link between circadian clock gene and preeclampsia could offer a novel approach to our understanding of this multi-system disease specific to pregnancy.